Histamine promotes adhesion of neutrophils by inhibition of autophagy in dairy cows with subacute ruminal acidosis - Kexin Wang; Zhenai Sun; Yunfei Li; Mingchao Liu; Juan J. Loor; Qianming Jiang; Guowen Liu; Zhe Wang; Yuxiang Song; Xinwei Li (Journal of Dairy Science, 2022)
ABSTRACT: Subacute ruminal acidosis (SARA), a common digestive disease in dairy cows, is accompanied by systemic inflammation and high concentrations of histamine in blood. Histamine-induced neutrophil adhesion may play an important role in the systemic inflammation experienced by cows during SARA. Autophagy, an intracellular degradation system, regulates recycling of membrane-associated integrin and may be involved in histamine-induced adhesion of bovine neutrophils. In the present study, 20 multiparous mid-lactation cows (average body weight 486 ± 24 kg) fitted with ruminal fistula were assigned to a control group (n = 10) or a SARA group (n = 10). We induced SARA by feeding different combinations of wheat-barley pellets and chopped alfalfa hay for 8 wk; SARA was defined as a ruminal pH <5.6 for at least 3 h/d. Blood samples were collected in wk 8. Compared with controls, SARA cows had greater serum concentrations of tumor necrosis factor-α, IL-6, IL-1β, lipopolysaccharide (LPS)-binding protein, haptoglobin, and serum amyloid A. Serum concentrations of these proinflammatory factors had strong positive correlations with the concentration of serum histamine and LPS. In ex vivo adhesion experiments, the number of adherent neutrophils was greater in the SARA group. Additionally, membrane protein abundance of adhesion molecules such as integrin α-L precursor (CD11a) and integrin α-M precursor (CD11b) was greater in neutrophils of the SARA group, confirming enhanced adhesion ability. Neutrophils of SARA cows had greater number of autophagosomes, greater protein abundance of autophagy substrate sequestosome-1 (p62), and higher ratio of microtubule associated proteins 1A/1B light chain 3 (LC3)-II to LC3-I, indicating congestion during the late phase of autophagy flux. For in vitro experiments, neutrophils isolated from control cows were incubated with 0.4 endotoxin units (EU)/mL LPS or 7 μM histamine for 0, 1, 2, and 4 h, respectively. We detected linear and quadratic effects for the number of adherent neutrophils after histamine treatment with a peak response at 2 h, whereas no significant effect was detected after LPS treatment. Membrane protein abundance of CD11a and CD11b was greater after histamine treatment, suggesting that it may have an inhibitory effect on the degradation of adhesion molecules. The greater abundance of p62, higher ratio of LC3-II to LC3-I, and increased co-localization between CD11b and LC3 after histamine treatment indicated that recycling of adhesion molecules and autophagy flux were blocked. These effects were not aggravated further in the presence of chloroquine, a specific inhibitor of the late phase of autophagy flux. Overall, our results revealed that histamine increases adhesion of neutrophils by inhibiting autophagy in dairy cows with SARA.